The Thermal [2+2] Cyclodimerisation of (E,Z)-Cycloocta-1,3-diene Revisited − Chemical Trapping and Properties of the Intermediate 1,4-Diradicals - Leitich, Johannes; Heise, Ingeborg; Angermund, Klaus; Rust, Jörg (European journal of organic chemistry, 2002)
The thermal [2+2] cyclodimerisation of (E,Z)‐cycloocta‐1,3‐diene (9), which is known to afford the cyclobutane dimers 11, 12, and 13, has been investigated in the presence of the nitroxyls 17 and 18 and of atmospheric dioxygen, all of which are known to be efficient trapping agents for carbon‐centred free radicals. The nitroxyls have been found to divert the reaction from formation of the dimers to formation of 2:2 adducts of two molecules of 9 and two molecules of nitroxyl. The rate constant for the formation of the overall sum of the dimers plus the 2:2 adducts in the presence of nitroxyl has been found to equal the rate constant for the formation of dimers in the absence of nitroxyl. This and the molecular structures of the 2:2 adducts prove that two molecules of 9 combine irreversibly to produce the two epimeric bis(allylic) 1,4‐diradicals 14 and 15 (meso and rac, respectively) which undergo two competing reactions: ring‐closure to dimers 11, 12, and 13, and trapping by nitroxyl to form the 2:2 adducts. Dioxygen, too, was found to trap 14 and 15 efficiently. From the kinetics of the latter trapping reaction, studied at six temperatures between 5 and 55 °C, the heights of the activation barriers separating 14 from 11 and 15 from 12 + 13 were estimated at 11.1 ± 1.5 and 10.2 ± 1.5 kcal·mol−1, respectively, corresponding to diradical lifetimes of ca. 0.5 μs. These unexpectedly high barriers have been verified by MM3 force‐field calculations and by an investigation of the kinetics of the gas‐phase thermolysis of 12 (to give 13 and 16 which is an epimer of 12 and 13) and of 13 (to give 12 and 16). When the cyclodimerisation of 9 was carried out in the presence of spin = 1/2 transition metal complexes, no trapping was observed, but a shift in the 12/13 ratio, resulting from a catalysed conversion of 15 from its singlet to its triplet spin state, was seen. Since nitroxyl also catalysed the singlet‐to‐triplet conversion (dioxygen did not) in competition with trapping, the kinetics of trapping by nitroxyl was complex, but it did show that 14 and 15 were jeopardised to trapping twice in their lifetimes, meaning that 14 and 15 were generated in their anti conformations, which had to change to the gauche conformations by crossing the barriers referred to above before they could ring‐close to dimers; all the anti and the triplet gauche conformations are trappable, but the singlet gauche conformations are not. The same conclusion was reached for 15 from independent experimental evidence. In addition, there is a minor path from 9 to dimers 11, 12, and 13, which is not subject to trapping and which involves the direct formation of the singlet gauche conformers of 14 and 15 from 9. The gauche conformer formed in the smallest amount along this minor pathway is the one giving rise to 12, which is the one with its two radical p‐orbitals pointing towards each other most strongly, thus causing adverse Woodward−Hoffmann effects. The direct formation of the principal gauche conformer (which gives rise to 13) from 9 requires 2.75 ± 0.44 and 2.57 ± 0.42 kcal·mol−1 more activation energy than required for the formation of the anti conformers of 14 and 15, respectively.